2017
DOI: 10.1128/aac.00931-17
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Study of Clinical Features of Breakthrough Acinetobacter Bacteremia during Carbapenem Therapy

Abstract: Breakthrough bacteremia during carbapenem therapy is not uncommon, and it creates therapeutic dilemmas for clinicians. This study was conducted to evaluate the clinical and microbiological characteristics of breakthrough bacteremia during carbapenem therapy and to assess the efficacy of various antimicrobial therapies. We analyzed 100 adults who developed breakthrough bacteremia during carbapenem therapy at 4 medical centers over a 6-year period. Their 30-day mortality rate was 57.0%, and the carbapenem resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…In fact, breakthrough A. baumannii complex bacteremia during carbapenem therapy have been observed [21, 22]. Thus, our findings that prior carbapenems exposure as an independent risk factor for CRAB BSI are consistent with those observations.…”
Section: Discussionsupporting
confidence: 90%
“…In fact, breakthrough A. baumannii complex bacteremia during carbapenem therapy have been observed [21, 22]. Thus, our findings that prior carbapenems exposure as an independent risk factor for CRAB BSI are consistent with those observations.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, its use in VAP was hampered when a phase III RCT showed tigecycline to be inferior to the comparator drug and to have higher mortality rates for VAP patients (17). The results from several recent studies and a meta-analysis are in line with these discouraging results (18)(19)(20), and these combined with increasing rates of tigecycline resistance among CRAB disfavor its use.…”
mentioning
confidence: 99%
“…The effectiveness of tigecycline for pneumonia has been called into question by observational and meta-analyses where an increase in mortality has been observed, including in patients with CRAB pneumonia [42][43][44][45]. Although subsequent, nonrandomized studies have suggested that high dose tigecycline may mitigate this effect [46,47], these studies were conducted with combination therapy making it difficult to assess tigecycline monotherapy.…”
Section: Tetracycline Derivativesmentioning
confidence: 99%